Investment outlook for the medium range tankers (MRs) segment from 2019 – 2023 - Li, Shuangcheng (2019)
Among the various investment opportunities, shipping has always been an area of interest to investors. However, shipping is made up of many different segments and each segment may demonstrate its own profit and risk profile, making it necessary to study them separately. This project seeks to explore the attractiveness of investment in one specific segment, the MR tanker segment, with an investment horizon from 2019 to 2023. It is approached from the perspective of an investor conducting a feasibility study into supporting a group of established shipping professionals who are soliciting for financial support to acquire a fleet of five 2015-built vessels. The project will be divided into three phases. Phase I explores on the surface the historical performances of MR tanker segment and MR shipping companies from 2007 to 2018 in order to find out if the segment is worth investing in, and results show that the MR tanker segment has very low returns compared to other investment opportunities and that the freight rates is the key driver to its performance. Phase II dives deeper into how the market fundamentals will perform from 2019 to 2023 by scanning the shipping environment and establishing projections of freight market performances in order to find out whether the MR tanker segment will improve or worsen. It has been found out that the market is improving from a weak market to a steadier position because demand is increasing at a faster pace than supply. Lastly, Phase III determines whether the market fundamentals will result in a higher intrinsic value than market value by computing the future earnings under different asset acquisition and deployment strategies. Results show that three ships should be purchased, and two ships should be time-chartered in. They should be deployed on a time-charter basis for either one-year time-charter for five years or a mix of one-year time-charter and three-year time-charter, without trading them in spot market. The results from this project will assist the investors in getting a comprehensive picture of MR tanker segment and hopefully help them to make the best investment decision possible.